Macro and micro functional components of a spreadable olive by‐product (pâté) generated by new concept of two‐phase decanter. Issue 1 (15th December 2016) - Lozano‐Sánchez, Jesús; Bendini, Alessandra; Di Lecce, Giuseppe; Valli, Enrico; Gallina Toschi, Tullia; Segura‐Carretero, Antonio
Abstract : In this research, the potential use of a spreadable olive by‐product, so called "pâté, " generated during a modern two‐phase centrifugal processing technique as a natural source of bioactive compounds has been evaluated using advanced separation techniques. For this purpose, the qualitative and quantitative characterization of the lipophilic and hydrophilic fractions were performed to establish the fatty acid composition and phenolic profile of the new spreadable olive by‐product. A typical olive oil fatty acid profile and very high oxidative stability was found for lipid fraction, whereas hydrophilic fraction was characterized by the presence of hydroxytyrosol, ß‐hydroxyverbascoside, oleoside derivative, luteolin, among other. This kind of compounds are well‐known for their beneficial effects in the human health. These results suggest that the spreadable olive by‐product could be used as functional ingredients, in the production of nutraceuticals or for feed industry. Practical applications: Application of analytical chemistry aimed at utilizing a new olive‐oil by‐product, either through conversion into an affordable source of bioactive compounds and in promoting their overall sustainable management. The obtained results indicate that this by‐product is a potential source of bioactive compounds with applications in the pre‐formulation of functional ingredient for human and animal feeding. The modern two‐phase centrifuge generates a new spreadable olive by‐product which consists of lipophilic and hydrophilic fractions. The analysis of lipophilic compounds showed a typical olive oil fatty acid profile and very high oxidative stability. Hydrophilic fraction was characterized by the presence of hydroxytyrosol, ß‐hydroxyverbascoside, oleoside derivative, luteolin, among other. This kind of compounds are well‐known for their beneficial effects in the human health. These results suggest that the spreadable olive by‐product could be used as functional ingredients, in the production of nutraceuticals or for feed industry. Abstract : The modern two‐phase centrifuge generates a new spreadable olive by‐product which consists of lipophilic and hydrophilic fractions. The analysis of lipophilic compounds showed a typical olive oil fatty acid profile and very high oxidative stability. Hydrophilic fraction was characterized by the presence of hydroxytyrosol, ß‐hydroxyverbascoside, oleoside derivative, luteolin, among other. This kind of compounds are well‐known for their beneficial effects in the human health. These results suggest that the spreadable olive by‐product could be used as functional ingredients, in the production of nutraceuticals or for feed industry.